Studi Komparasi Kinerja Daya Tarik Institutional dan Keunikan Kapabilitas Sumber Daya terhadap Kinerja Perguruan Tinggi Muhammadiyah Provinsi Jambi dengan Perguruan Tinggi Muhammadiyah Provinsi Sumatera Barat - Arman Syafa’at; Mustika Mustika; Andri Devita; Puja Mahrani (Universitas Batanghari Jambi, 2026)
This study aims to analyze the comparative effects of institutional attractiveness and uniqueness of resource capabilities on the performance of Muhammadiyah Higher Education Institutions (PTM) in Jambi and West Sumatra Provinces. A quantitative approach with a cross-sectional comparative design was employed. Data were collected from 40 permanent lecturers (20 respondents from each province) through questionnaires and supported by secondary data. The data were analyzed using independent samples t-test and multiple linear regression with SPSS 21. The results indicate significant differences across all variables, with PTM in West Sumatra outperforming those in Jambi. Uniqueness of resource capabilities has a positive and significant effect on PTM performance (β = 0.535; p = 0.007), while institutional attractiveness shows a positive but insignificant effect (β = 0.308; p = 0.080). These findings support the Resource-Based View, which emphasizes internal capabilities as the primary determinant of performance, and align with the Balanced Scorecard framework. Therefore, strategies to enhance PTM competitiveness should focus on strengthening human resources, research productivity, and Al-Islam Kemuhammadiyahan values, supported by mentoring policies within the Muhammadiyah network.